THE RETURN PROCEEDINGS OF THE JURY: UNANIMOUS DECISION OR VOTING? - I. Ermakova (Russian Journal of Economics and Law, 2009)
The article analyzes the Russian Criminal Code norms and scientific works concerning the rules of the jury's conference and voting during the return proceedings, the author also gives a short overview of several foreign states' legislation regulating this aspect. An original model of the jury's voting is suggested.